Fusarium wilt caused by Fusarium oxysporum f. sp. cubense tropical race 4 in banana plantations in Türkiye - Mümine ÖZARSLANDAN; Davut Soner AKGÜL (Phytopathologia Mediterranea)
important disease for banana production. Presence and prevalence of FocTR4 in banana plantations on the Mediterranean coast of Türkiye were assessed during 2018 to 2020 in a total of 117 banana plantations in open fields and protected plastic greenhouses. Rhizome, pseudostem, and root samples were taken from plants showing typical symptoms associated to the disease and from suspected affected plants. Fungi were isolated from the plant internal tissues, and Fusarium oxysporum-like colonies were sub-cultured for further analyses. Phylogenetic analyses of 36 isolates showed that they belonged to four different Fusarium species: F. musae, F. oxysporum, F. sacchari, and F. solani. Eight representative F. oxysporum isolates were identified as FocTR4 by specific PCR and qPCR tests. Pathogenicity tests were carried out on tissue-cultured ‘Cavendish’ type banana seedlings (‘Grand Naine’) for 36 Fusarium isolates, and their virulence was assessed based on the internal necrosis observed in the rhizomes. Approx. 40 to 65 d after inoculations, FocTR4, F. oxysporum, and F. sacchari isolates caused severe to mild necroses in the seedling rhizomes. This is the first report of F. sacchari associated with root and collar rot of bananas in Türkiye. This study showed that Fusarium wilt caused by FocTR4 is present, but at low incidence (6.8%) in Turkish banana plantations.